Screen acting skills a practical handbook for students and tutors - Wooster, Roger; Conway, Paul (Dramatist) (Methuen Drama/Bloomsbury Publishing Plc, 2020)
Screen Acting Skills offers up advice and practical screen acting exercises aimed at students seeking clear, practical exercises to aid them in their study. The book addresses the fact that many screen actors beginning their careers lack the necessary pre-shoot preparation and knowledge of studio protocols that are required of them, and aims to augment existing theoretical and academic studies by offering practical, focussed exercises that can be explored in low-tech workshop situations. Written in an informal, accessible, jargon-free and often humorous style, Screen Acting Skills enables creativity on the studio or workshop floor, allowing young actors to access their own talent, and to discover and hone their skills in preparation for future training and a career. Through the exercises and the overall approach, the reader is offered a fresh, low-tech and yet highly relevant professional approach to early screen acting training and studio work. The book is published alongside online videos of workshops with screen acting students"--